'Almost Everything in the House Now Is Plastic': Foregrounding Plastic Materiality in Household Routines and Practices. (March 2023) - Shittu, Olamide
The impact of materials in disrupting routines and practices has recently become significant in scholarship and policymaking. This has motivated alternative social theories such as practice theory to look beyond the traditional human behavioural approaches into how objects exert their materiality in achieving daily activities. While there is a substantial theoretical body of work on materiality in practice theory, this study focuses on plastic and asks how plastic facilitates the reproduction of practices in households. To foreground plastic materiality, this study makes use of the data collected in the case studies of low-income households in a suburb in Lagos, Nigeria through a mixed-methods approach, including interviews, household tours, and directed photography. The data analysis combines inductive and deductive approaches to facilitate an iterative process of identifying and refining themes related to the research aim. As a ubiquitous material, plastic facilitates the performance of household practices related to hygiene, comfortability, storage, food, and child-rearing, among others. By interacting with other practice elements, plastic actively materialises household routines through its corporality or physical features, functionality, and spatiotemporal quality. The implication of these dimensions in enabling or disrupting household routines is further discussed. The findings present important lessons for advancing the corporal and relational dimensions of materiality in social theory and implementing sustainability policies.